ANALYSIS OF THE GOVERNMENT POLICY RESEARCHIN INDONESIAN MARKET - Yoga Pandalungan Wiro Menggolo; Yogi Septian E (AIBPM Publisher, 2018)
The purpose of this study is to observe how big the effect of government policy that does notallow foreign products to enter Indonesia so that the impact on the economy in the Indonesianmarket. Itis important for us to conduct this research because Indonesia is involved in thedevelopment ofthe global economy (free market) so as to cause various impacts on theIndonesian market. Data obtained from the interview of one of the owners of the business ofselling baby clothes. The analytical method by collecting data from the owner of a babyclothing seller, extracts data from several sources on government policy. Then analyze theresults of the data collection to getconclusions about government policy research inIndonesian Market.